Funding agencies in low- and middle-income countries: Support for knowledge translation - Cordero, Cynthia; Delino, Rachel; Jeyaseelan, L.; Lansang, Mary Ann; Lozano, Juan M.; Kumar, Shuba; Moreno, Socorro; Pietersen, Merle; Quirino, Jose; Thamlikitkul, Visanu; Welch, Vivian A.; Tetroe, Jacqueline; et al. (My University, 2008)
Objective: The aim was to describe how selected health research funding agencies active in low- and middle-income countries promote the translation of their funded research into policy and practice. Methods: We conducted inductive analysis of semi-structured interviews with key informants from a purposive sample of 23 national and international funding agencies that fund health research in Brazil, Colombia, India, the Philippines, South Africa and Thailand. We also surveyed web sites. Findings: We found a commitment to knowledge translation in the mandate of 18 of 23 agencies. However, there was a lack of common terminology. Most of the activities were traditional efforts to disseminate to a broad audience, for example using web sites and publications. In addition, more than half (13 of 23) of the agencies encouraged linkage/exchange between researchers and potential users, and 6 of 23 agencies described pull activities to generate interest in research from decision-makers. One-third (9 of 23) of funding agencies described a mandate to enhance health equity through improving knowledge translation. Only 3 of 23 agencies were able to describe evaluation of knowledge translation activities. Furthermore, we found national funding agencies made greater knowledge translation efforts when compared to international agencies. Conclusion: Funding agencies are engaged in a wide range of creative knowledge translation activities. They might consider their role as knowledge brokers, with an ability to promote research syntheses and a focus on health equity. There is an urgent need to evaluate the knowledge translation activities of funding agencies.